Structural and epistatic regulatory variants cause hallmark white spotting in cattle - Jivanji S; Wilkinson E; Tang L; Tiplady KM; Yeates A; Harland C; Gray C; Couldrey C; Worth G; Gamache I; Desjardins J; Tabares JAA; et al. (American Association for the Advancement of Science, 2025)
Despite being one of the most iconic and immediately recognizable traits in domestic cattle, the variants underpinning the white-spotted coat pattern of Holstein-Friesian and related breeds remain uncharacterized. Here, we report two variants modulating these effects, comprising intronic and long-distance-acting regulatory variants of the MITF and KIT genes. We confirm causality through "Holsteinized" mouse models edited for these alleles and show that these variants are likely responsible for spotting traits in other bovine breeds. These effects include epistatic impacts on other bovine coat patterns, such as fine-scale speckling, "black socks," and reversal of the otherwise dominant, "white-face" trait characteristic of Hereford cattle.